PENERAPAN ACTIVITY BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA PT. PERKEBUNAN NUSANTARA IV PABRIK TEH SIDAMANIK UNIT TOBASARI - Purba, Maria Verany; Silalahi, Evelin Roma Riauli (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to determine the application of Activity Based Management in increasing production cost efficiency at PT. Perkebunan Nusantara IV Sidamanik Tea Factory. The population in this research is Production Costs, Non-Production Costs, and production activity data starting from the founding of the company from 1979 until now. The samples used in this research are Production Costs, Non-Production Costs, and production activity data for 2022. The data analysis technique used is qualitative descriptive analysis. Based on the results of the analysis and eval_uation, it can be concluded that the realization of production costs for each element of production costs using the Traditional method costs realization of IDR 175.276.450.452. Meanwhile the realization of production costs using the Activity Based Management method costs realization of IDR 169.616.770.368. Based on a comparison of the two methods, it can be seen that the cost difference is IDR 5.659.680.084. It can be seen that by implementing Activity Based Management you can identify value-added activities and non-value-added activities. So the level of production cost efficiency using the Company's Activity Based Management method can save costs of up to 3.22%. Therefore, companies need to apply the Activity Based Management method to eliminate non-value-added activities so that production cost efficiency can be achieved.